La exclusión de los elementos materiales probatorios y evidencias físicas en el sistema procesal penal con tendencia acusatoria - Cabrera Saavedra, Omar (Universidad de San Buenaventura - Cali, 2016)
This paper on the exclusion of the evidentiary material element and physical evidence in the Act 906 of 2004, which incorporated into our legislation the criminal procedural system of adversarial court aims to find reasons that allow their exclusion within the criminal proceedings. They must find reasons to the exclusion of evidence in criminal proceedings, conducting a review of the main sources of the criminal law, these are: the political Constitution of 1991, Act 906 of 2004 and the relevant jurisprudence on the subject made by the Constitutional Court and Supreme Court. We anticipate that judicial practice demonstrates that though so are supplied devices to safeguard rights and fundamental guarantees of the processed person liable, there is violation of these rights when elements evidentiary materials and physical evidence that potentially unlawful decisions affecting the processed person.